Mempengaruhi Keputusan Calon Pelamar CPNS Dosen Melalui Webinar Kiat Sukses Memilih Formasi - Wangsa, Arma; Naing, Ince Rezky; Yansa, Hajra; Salido, Achmad; Rahman, Gusti Arviana; Firdaus, Andi Mulawakkan; Wijaya, Ariyadi (Lembaga Dongan Dosen, 2024)
There are prospective applicants for Civil Servant Candidate (CPNS) positions, particularly for lecturer roles, who still feel uncertain about the formations they plan to apply for. This uncertainty stems from several factors, including the time and selection process, the number of available positions, the number of applicants, and the passing score threshold. In light of these considerations, this article seeks to explain how the webinar on tips for successfully choosing lecturer formations influenced the decisions of prospective CPNS applicants in selecting a formation. The webinar was conducted in three main phases: pre-implementation, implementation, and evaluation. The results of this community service initiative show that the webinar influenced the decisions of prospective CPNS lecturer applicants in choosing a formation. Before attending the webinar, only about 30.8% felt confident in their decision, but after attending, this percentage increased to around 93.3%. Participants who were initially unsure about their choices became more confident after the webinar, with two main outcomes. The first was that participants became more confident in their original choice, and the second was that participants felt confident to switch to another formation.